(untitled) (Tzintzun, Revista de Estudios Históricos, 2024)
n the core of power of the Francoist dictatorship, they were aware that in order to completely wipe out the legacy of the Second Republic, weapons alone were not enough. It was in this context that the regime’s ideologues considered that the only way to erase the republican culture from memory, and to begin the ideological process of restoring the empire and Hispanic culture, was to transfer the war to a new field: education. On this battlefield, the history textbooks of Franco’s baccalaureate became the ideal instruments for rooting in the imagination of Spanish students the project of nation and national identity that the Franco regime sought to perpetuate. In particular, to achieve the creation of a “New Man” in charge of building the “New Spain”. For this paper we carried out a historical and historiographical analysis of how Franco’s school textbooks interpreted and justified the loss of the American Empire, paying special attention to the Mexican insurgent process.